Cerebroprotein Hydrolysate-I Inhibits Hippocampal Neuronal Apoptosis by Activating PI3K/Akt Signaling Pathway in Vascular Dementia Mice - Wu X (Dove Medical Press, 2021)
Xiaolin Wu,1,2 Yingjuan Liu,2 Lin Zhu,2 Yue Wang,2 Yuqian Ren,2 Baohe Cheng,3 Leiming Ren,4 Keli Ge,2 Hongyun Li1 1Department of Neurology, The Affiliated Hospital of Qingdao University, Qingdao, Shandong, 266003, People’s Republic of China; 2Institute of Integrative Medicine, School of Basic Medicine, Qingdao University, Qingdao, Shandong, 266021, People’s Republic of China; 3Shandong Haoyun Guoji Stem Cells Hospital, Jinan, Shandong, 250001, People’s Republic of China; 4Institute of Chinese Integrative Medicine, Hebei Medical University, Shijiazhuang, Hebei, 050017, People’s Republic of ChinaCorrespondence: Hongyun LiDepartment of Neurology, The Affiliated Hospital of Qingdao University, No. 16, Jiangsu Road, Shinan District, Qingdao, Shandong, People’s Republic of ChinaEmail 18661808653@163.comKeli GeInstitute of Integrative Medicine, School of Basic Medicine, Qingdao University, No. 38, Dengzhou Road, Shibei District, Qingdao, Shandong, People’s Republic of ChinaEmail ntfadu@163.comIntroduction: Vascular dementia (VaD), one of the brain injuries, is difficult to be cured, so it is important to take active neuroprotective treatment after its occurrence. Many studies have shown that apoptosis serves an important role in VaD occurrence; therefore, inhibition of apoptosis may contribute to the recovery of neurological function after VaD occurrence. Cerebroprotein hydrolysate-I (CH-I), a neuropeptide preparation which consists of several amino acids and small molecular peptides as the main active constituent, is extracted using a method similar to cerebrolysin (CBL) which has neuroprotective and neurotrophic effects.Methods: In the present study, a VaD model which was constructed using bilateral common carotid artery occlusion (BCCAO) in Kunming mice was applied to examine the neuroprotective effects of CH-I.Results: The results show that CH-I treatment could attenuate the decrease of learning and memory ability, cell apoptosis in the hippocampal CA1 region and inhibit the activation of caspase-3 and caspase-9 in VaD mice. Furthermore, CH-I treatment could also upregulate Bcl-2 protein levels and activate PI3K and Akt.Discussion: We speculate that CH-I may induce a neuroprotective effect activating PI3K/Akt signaling pathway in VaD mice.Keywords: vascular dementia, cerebroprotein hydrolysate-I, apoptosis, PI3K/Akt